2018
DOI: 10.1088/0256-307x/35/10/104301
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Multi Emission Lens via Transformation Acoustics

Abstract: Based on transformation acoustic methodology, we propose an algorithm for designing acoustic non-resonant lens antenna, which is competent to generate multiple directive beams that are pointing at the desired direction. Unattainable with previous works, the present approach is capable of adjusting the directivity of each radiated beam individually, which is of the utmost importance in several acoustic applications such as in sonar systems. A linear transformation function is intentionally used for eliminating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It was shown that these materials are achieved via transforming an original domain (named as virtual space) into the transformed domain (expressed by physical space) with an appropriate mapping function [7]. Since the introduction of this innovative method, many novel acoustic devices that were deemed impossible to be achieved such as acoustic rotators [8], illusion devices [9], acoustic beam collimating lenses [10] and acoustic cloaks [11] have been realized and experimentally demonstrated with acoustic metamaterials. In addition to the mentioned applications, several TA-based devices have been reported for focusing the acoustic waves in a specific volume of space [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that these materials are achieved via transforming an original domain (named as virtual space) into the transformed domain (expressed by physical space) with an appropriate mapping function [7]. Since the introduction of this innovative method, many novel acoustic devices that were deemed impossible to be achieved such as acoustic rotators [8], illusion devices [9], acoustic beam collimating lenses [10] and acoustic cloaks [11] have been realized and experimentally demonstrated with acoustic metamaterials. In addition to the mentioned applications, several TA-based devices have been reported for focusing the acoustic waves in a specific volume of space [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…AS an ingenious mathematical approach, transformation optics (TO) [1][2][3][4][5][6] provides a powerful and convenient way to control the electromagnetic (EM) fields arbitrarily, arousing much attentions in the past two decades. Based on this methodology, novel devices with varied functions and applications have been proposed, designed and experimented with an unprecedented prosperity, including invisible cloaks [7][8][9][10][11][12][13], concentrators [14][15][16][17][18], illusory devices [19][20][21][22][23][24][25][26][27][28] and antennas [29][30][31][32][33][34][35] etc. The most striking device among them is invisible cloak, where some properly designed materials are utilized to direct the EM waves propagates smoothly around an arbitrarily shaped object, making the entire device (including the coated object) become invisible for the outside viewers.…”
Section: Introductionmentioning
confidence: 99%